2016
DOI: 10.1039/c6ra06307a
|View full text |Cite
|
Sign up to set email alerts
|

Improving the surface-enhanced Raman scattering activity of carbon nitride by two-step calcining

Abstract: The modified g-C3N4 substrates were prepared by a two-step calcining method. The morphologies and microstructures of modified g-C3N4 were successfully controlled. The modified g-C3N4-2 h + Ag substrate exhibited superior SERS activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
(24 reference statements)
3
7
0
Order By: Relevance
“…Moreover, the higher weight loss of the uC and tC samples at 200 °C < T < T onset reveals that these samples contain a large amount of low-molecular-weight components (LMWC). After T onset points, weight loss drops to zero at T = 600–650 °C for pristine g-C 3 N 4 , which is in agreement with other reports. ,, However, the thermal stability in the composites tends to differ from pristine g-C 3 N 4 . The T onset values for the composites are tCNT (434 °C) > dCNT (411 °C) > mCNT (396 °C) > uCNT (264 °C).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the higher weight loss of the uC and tC samples at 200 °C < T < T onset reveals that these samples contain a large amount of low-molecular-weight components (LMWC). After T onset points, weight loss drops to zero at T = 600–650 °C for pristine g-C 3 N 4 , which is in agreement with other reports. ,, However, the thermal stability in the composites tends to differ from pristine g-C 3 N 4 . The T onset values for the composites are tCNT (434 °C) > dCNT (411 °C) > mCNT (396 °C) > uCNT (264 °C).…”
Section: Resultssupporting
confidence: 92%
“…After T onset points, weight loss drops to zero at T = 600−650 °C for pristine g-C 3 N 4 , which is in agreement with other reports. 25,39,46 However, the thermal stability in the composites tends to differ from pristine g-C 3 N 4 . The T onset values for the composites are tCNT (434 °C) > dCNT (411 °C) > mCNT (396 °C) > uCNT (264 °C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Note that the thermal stability of CN materials somewhat differs between different preparation methods, which may be due to different degrees of condensation and different packing motifs. 97 So the TGA results directly confirmed that the modified g-C 3 N 4 with a different calcining time possessed different degrees of polymerization, well consistent with the FT-IR results. Fig.…”
Section: Properties Of G-c 3 Nsupporting
confidence: 83%
“…Consistent with the XRD analysis results, with increased calcination time the g-C 3 N 4 became atter. However, aer 2-3 h of heating, the g-C 3 N 4 went through partial re-aggregation and was then damaged by thermal effects, 58 as Fig. 4(f) demonstrates.…”
Section: Resultsmentioning
confidence: 94%